2020
DOI: 10.3390/en13020395
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Approach to the Exergy Destruction and the Simple Expansion Work Potential in the Constant Internal Energy and Volume Combustion Process

Abstract: The exergy destruction due to the irreversibility of the combustion process has been regarded as one of the key losses of an internal combustion engine. However, there has been little discussion on the direct relationship between the exergy destruction and the work output potential of an engine. In this study, an analytical approach is applied to discuss the relationship between the exergy destruction and efficiency by assuming a simple thermodynamic system simulating an internal combustion engine operation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The highest exergy destruction rates and costs also occurred in the engine studied by Reference [77], but as mentioned by References [78,79], are inherent to the combustion process. Reference [80] investigated the factors affecting exergy destruction and identified that the most sensitive parameters for ICE were the thermodynamic state before combustion and the fuel employed.…”
Section: Exergoeconomic Resultsmentioning
confidence: 99%
“…The highest exergy destruction rates and costs also occurred in the engine studied by Reference [77], but as mentioned by References [78,79], are inherent to the combustion process. Reference [80] investigated the factors affecting exergy destruction and identified that the most sensitive parameters for ICE were the thermodynamic state before combustion and the fuel employed.…”
Section: Exergoeconomic Resultsmentioning
confidence: 99%
“…[1] presents an advanced exergoeconomic analysis of a waste heat recovery system based on the organic Rankine cycle from the exhaust gases of an internal combustion engine considering different operating conditions; ref. [2] uses an analytical approach to discuss the relationship between the exergy destruction and efficiency by assuming a simple thermodynamic system simulating an internal combustion engine operation; ref. [3] applies the Exergy Cost Theory to a hybrid system based on a 500 kWe solid oxide fuel cell stack and on a vapor-absorption refrigeration system by a model comprising chemical, electrochemical, thermodynamic, and thermoeconomic equations and using the Engineering Equation Solver; ref.…”
Section: Introductionmentioning
confidence: 99%